Detection of intracranial aneurysms with unenhanced and echo contrast enhanced transcranial power Doppler. Issue 4 (1st April 2000) - Turner, Carole L; Kirkpatrick, Peter J
Abstract : OBJECTIVE: To assess transcranial power Doppler and the effect of an intravenous ultrasonic contrast agent for detecting intracranial aneurysms in patients admitted with a subarachnoid haemorrhage METHODS: 203 patients with subarachnoid haemorrhage were examined with the operator blind to the results of the admission CT and subsequent digital subtraction angiogram (DSA). In 98 cases patients were imaged using unenhanced transcranial power Doppler, and in 105 cases, patients were imaged both using unenhanced and echo contrast enhanced (Levovist, Schering AG) transcranial power Doppler. RESULTS: DSA detected 168 intracranial aneurysms in 128 patients (24 patients had multiple lesions) and 75 patients had an aneurysm negative DSA. There was agreement between DSA and transcranial power Doppler in 87 intracranial aneurysms of which 20 were only detected after infusion of contrast agent. Without contrast infusion, transcranial power Doppler showed a sensitivity of 40% and specificity of 91%. A significant increase in detection was noted when using a contrast agent (χ 2 =9.49, p<0.001). With a contrast study the sensitivity increased to 55% with a specificity of 83%. Intracranial aneurysm detection by transcranial power Doppler was significantly dependent on position using a contrast infusion (χ 2 =15.87, p<0.05). A positive correlation was also found between the size of intracranial aneurysms measured by transcranial power Doppler and DSA ( r =0.55, p<0.05). The transcranial power Doppler sensitivity and specificity increased with larger aneurysms and reached 100% for intracranial aneurysms greater than 12 mm diameter. Detection by transcranial power Doppler was also dependent on morphology (χ 2 =14.46, p<0.001). CONCLUSIONS: The detection of intracranial aneurysm by transcranial power Doppler is dependent on aneurysm location, size, and morphology and is enhanced with the use of an intravenous contrast agent.